2022
DOI: 10.34172/jpd.2022.11161
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of thyroid status with severity and mortality of COVID-19 patients

Abstract: Introduction: Thyroid status because of the expression of angiotensin-converting enzyme-2 (ACE2), which is a functional receptor for coronavirus disease 2019 (COVID-19) in thyroid glands, maybe affects COVID-19 patients’ outcomes. Objectives: This study aimed to evaluate the correlation of thyroid status with the severity and mortality of COVID-19 patients. Patients and Methods: In a retrospective cohort study conducted on 521 COVID-19 patients, data were collected by a demographic questionnaire and a checklis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…According to the result of this retrospective cohort study, thyroid status is not related to the severity of COVID-19 or its mortality. However, in contrast to this finding, a previous study showed the association between lower free triiodothyronine (FT3) with the severity of COVID-19 and mortality rate (1). Some mechanisms explain the changes in thyroid hormone in COVID-19 patients.…”
Section: Open Accessmentioning
confidence: 73%
See 1 more Smart Citation
“…According to the result of this retrospective cohort study, thyroid status is not related to the severity of COVID-19 or its mortality. However, in contrast to this finding, a previous study showed the association between lower free triiodothyronine (FT3) with the severity of COVID-19 and mortality rate (1). Some mechanisms explain the changes in thyroid hormone in COVID-19 patients.…”
Section: Open Accessmentioning
confidence: 73%
“…https://www.jparathyroid.com Journal of Parathyroid Disease 2022,10, e11187 of Commentary W e read the recently published article entitled "Correlation of thyroid status with severity and mortality of COVID-19 patients" with great attention (1). Although we believe the authors of this study have made a considerable contribution to this effort, we would like to add some additional comments.…”
Section: Open Accessmentioning
confidence: 96%